Development of a Clinical-Academic-Community Collaboration to Improve Health Literacy - Daniela B. Friedman (Journal of Primary Care & Community Health, 2020)
Limited health literacy is associated with poor patient health outcomes and increased hospitalization rates. Patient-provider communication plays an important role in patient health literacy and the understanding of medical terminology. This study demonstrates how a collaboration between clinical, academic, and community partners was instrumental in the design and implementation of a clinic readiness assessment and a clinic-based pilot intervention to encourage patient-provider communication and improve patient health literacy. A state hospital association, academic research team, and community adult literacy center director collaborated to develop a 60-item clinic readiness assessment and an evidence-informed pilot intervention. The clinic readiness assessment captured clinics’ motivation and capacity for pilot implementation and providers’ current communication strategies. The intervention centered around AskMe3™ educational materials and involved 2 patient visits (initial and follow-up visits). Data collection instruments for the intervention were administered verbally and included questions about patient demographics and communication needs, and a single-item health literacy measure. Descriptive statistics (frequencies/percentages) were used to analyze results from the clinic readiness assessment and pilot intervention. Establishment of the partnership, and collaborative, iterative development of the clinic readiness assessment and pilot intervention are described. This pilot project resulted in important lessons learned which led to critical modifications that will inform future expansion of the intervention. Collaboration between healthcare leaders, researchers, and community partners is recommended for developing clinic-based health literacy initiatives.